1990
DOI: 10.1128/mcb.10.2.770-776.1990
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotyrosine-Containing Lactate Dehydrogenase Is Restricted to the Nuclei of PC12 Pheochromocytoma Cells

Abstract: There are five lactate dehydrogenase (LDH) isoenzymes, composed of various combinations of two types of subunits. LDH-5, which contains only the LDH A subunit, is known to be present in both the cytoplasm and the nucleus, to act as a single-stranded DNA-binding protein possibly functioning in transcription and/or replication, and to undergo phosphorylation of tyrosine 238 in approximately 1% of the enzyme after cell transformation by certain tumor viruses. We have characterized LDH from wild-type PC12 pheochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, the majority of LDHA proteins and their activities are located in cytosolic fractions, which is in agreement with previous observations, e.g. from PC12 cells [43]. So far, there are at least two independent reports on the phosphorylation of LDHA at both serine and tyrosine residues [42,43].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the majority of LDHA proteins and their activities are located in cytosolic fractions, which is in agreement with previous observations, e.g. from PC12 cells [43]. So far, there are at least two independent reports on the phosphorylation of LDHA at both serine and tyrosine residues [42,43].…”
Section: Discussionsupporting
confidence: 92%
“…Despite several reports on the presence of LDHA in the nucleus [23,25,28,[42][43][44], it has conventionally been depicted as a cytosolic enzyme. Notably, immunohistochemistry stainings have revealed both cytoplasmic and nuclear LDHA expression in lung cancer cells [25,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathic pain is also accompanied by overexpression of HIF1α by ROS, hypoxia, and ischemia stimulation [ 68 , 69 , 70 ]. Previous studies have demonstrated that HIF1α signaling and ROS accumulation would regulate neuronal LDHA translocation [ 19 , 71 , 72 , 73 ]. Moreover, LDHA, as a transcription factor, can regulate VEGF gene expression and promote angiogenesis [ 74 ].…”
Section: Discussionmentioning
confidence: 99%